2020
DOI: 10.1111/btp.12858
|View full text |Cite
|
Sign up to set email alerts
|

Forest biomass stocks and dynamics across the subtropical Andes

Abstract: Forest biomass plays an important role in the global carbon cycle. Therefore, understanding the factors that control forest biomass stocks and dynamics is a key challenge in the context of global change. We analyzed data from 60 forest plots in the subtropical Andes (22–27.5° S and 300–2300 m asl) to describe patterns and identify drivers of aboveground biomass (AGB) stocks and dynamics. We found that AGB stocks remained roughly constant with elevation due to compensating changes in basal area (which increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Similarly, the interrelations between stand structure characteristics and precipitation were also observed in tropical seasonal forest. Nevertheless, the climate factors and BA did not jointly affect AGB in this biome, which has been revealed in other studies due to influences of the topography [104][105][106], soil properties, management protocols, and species diversity [107][108][109][110]. Additionally, we found that the contribution of climate and stand factors to AGB in tropical and temperate forests was greater than that in boreal forest, but the potential ecological reasons remained unclear on a large scale.…”
Section: Determinants Of Co-driving Agb Among Climate Stand Structura...supporting
confidence: 66%
“…Similarly, the interrelations between stand structure characteristics and precipitation were also observed in tropical seasonal forest. Nevertheless, the climate factors and BA did not jointly affect AGB in this biome, which has been revealed in other studies due to influences of the topography [104][105][106], soil properties, management protocols, and species diversity [107][108][109][110]. Additionally, we found that the contribution of climate and stand factors to AGB in tropical and temperate forests was greater than that in boreal forest, but the potential ecological reasons remained unclear on a large scale.…”
Section: Determinants Of Co-driving Agb Among Climate Stand Structura...supporting
confidence: 66%
“…Climate models that were only used to explore the impact of climate change on δ AGB exclusively included both MAT and annual precipitation as main predictors. A similar model structure was used in (Blundo et al, 2021). In the following section, we firstly present information on AGB stocks (Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Human activities have been swiftly transforming land cover patterns and their spatial arrangement [1]. Forest ecosystems, in particular, are profoundly affected by processes such as deforestation, excessive development, and land reclamation [2,3], leading to substantial changes in the spatial functionality of forest ecosystems, such as the eroded ecosystem services [4], and escalated threats to biodiversity [5]. Moreover, these alterations potentially hinder human society's progress and sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Unsustainable or negative forest exploitation and land use pattern transformation have substantially altered the spatial distribution and composition of existing forests, Forests 2023, 14, 2376 2 of 23 resulting in a progressive process of once-large and continuous forest patches converting into smaller, isolated forest remnants, which is a worldwide phenomenon known as forest fragmentation [5,6]. Forest fragmentation induces significant consequences, including the spread of diseases [7], abrupt shifts in microclimates at forest edges [8], increased forest fire occurrences [9], diminished habitat for species survival [10], increased greenhouse gas emissions [11], and the loss of biodiversity [12].…”
Section: Introductionmentioning
confidence: 99%